Tutela preventiva dos direitos de propriedade intelectual - Pinheiro, Rodrigo Gomes de Mendonça (2016)
In this dissertation we demonstrate that the intellectual property rights belong to a category historically overlooked by the legal system from several countries, which always have identified the possibility of monetization of these rights and the use of the compensatory tutelage as a preferred mechanism to resolve conflicts of this segment. However, we identified and this is the centerpiece of this research and dissertation that the accurate comprehension of the intellectual property rights in all aspects conducts to the conclusion of the adequate, effective and timely tutelage of these assets only occurs through the use of a differentiated judicial protection with preventive and inhibitory nature. In other words, protecting the intellectual property the competitive advantage of the holder also will be safeguarded in relation to the competition, to the personality rights of the creators and authors and to the values and attributes that are added to the holder who takes advantage of the intellectual properties as competition and business tools. To support this positioning, this dissertation is based in the national and foreign doctrine that more recently has recognized the existence of certain rights (also called new rights , among which are the intellectual property) whose outstanding feature is the insusceptibility pricing, making it impractical and inefficient conversion into money, especially when it is not possible objectively quantify it and also be unable to obtain full and adequate compensation for damage caused by the violation. Furthermore, we have identified many concrete cases in which the Brazilian Judiciary has not contributed to the desired primacy of the specific tutelage of the obligations by falling to observe that the freedom of choice and the individual freedom can be object of restriction, so that the rights of intellectual property are actually protected in appropriate, effective and timely way